New Technologies and the Gender Wage Gap: Evidence from France - Moreno-Galbis, Eva; Wolff, François-Charles (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
AbstractThis paper focuses on the impact of information and communication technologies (ICT) on the gender pay gap along the wage distribution. Our empirical analysis relies on two complementary French surveys conducted in 1998 and 2005 on a large sample of employees. We estimate quantile regressions and use a difference-in-difference strategy to assess the effect of new technologies. Both in 1998 and 2005, we find that the gender gap estimated for the group of ICT-users is not really different from the gap for non-users. Among ICT-users, wage differentials between men and women are mostly explained by a divergence in the rewards to identical characteristics.